2015
DOI: 10.1016/j.neurobiolaging.2014.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Integrated cortical structural marker for Alzheimer's disease

Abstract: In this paper we propose an approach to integrate cortical morphology measures for improving the discrimination of individuals with and without very mild AD. FreeSurfer was applied to scans collected from 83 participants with very mild AD and 124 cognitively normal individuals. We generated cortex thickness, white matter convexity (aka “sulcal depth”) and white matter surface metric distortion measures on a normalized surface atlas in this first study to integrate high resolution gray matter thickness and whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…In this study, our results in the standard LFO band by NBS showed several functional connections between different brain regions in DMN were decreased, while only two functional connections were increased. It was broadly consistent with the previous studies within the DMN in AD using multiple imaging techniques, and indicated AD might reduce the cognitive ability by impaired the functional connections in DMN ( Brier et al, 2012 ; Dubois et al, 2014 ; Zhong et al, 2014 ; Ming et al, 2015 ). The separation results in the four frequency bands demonstrated the altered functional connections were only in the slow-4 and slow-5 bands.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, our results in the standard LFO band by NBS showed several functional connections between different brain regions in DMN were decreased, while only two functional connections were increased. It was broadly consistent with the previous studies within the DMN in AD using multiple imaging techniques, and indicated AD might reduce the cognitive ability by impaired the functional connections in DMN ( Brier et al, 2012 ; Dubois et al, 2014 ; Zhong et al, 2014 ; Ming et al, 2015 ). The separation results in the four frequency bands demonstrated the altered functional connections were only in the slow-4 and slow-5 bands.…”
Section: Discussionsupporting
confidence: 91%
“…Those were only presented as exploratory results and should be confirmed in an independent sample. In parallel, data reduction strategies such as PCA were adopted to decrease the number of variables (Ming et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The sulcal shape abnormalities that are observed may be primarily affected by cortical atrophy, following the well-known progression of tau pathology in AD, 41 and by the reduction of gyral white matter volume. 42,43,44 .Further studies are needed to clarify this point and to investigate the role of sulcal shape abnormalities in the differential diagnosis of AD. Legend : A computer vision pipeline mimicking a human anatomist.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%